Peningkatan Higher Order Thinking Skill dan Kemampuan Kognitif pada Mahasiswa melalui Pendekatan Science, Environment, Technology and Society Berbantuan Modul Pembelajaran - Yulia Dewi Puspitasari; Purwo Adi Nugroho (JIPI (Jurnal IPA dan Pembelajaran IPA), 2020)
The background is the Higher order thinking skills of students that have not been developed to the maximum, the learning approaches used have not varied, and the lack of learning media. The cognitive abilities of students are also not yet developed. This study aims to: (1) Improve Higher Order Thinking Skills of Science Education students, (2) Increase Student Cognitive Ability. The research method used was Classroom Action Research with the Kurt Lewin model and the Collaborative Model with more than one cycle. Every cycle there are stages that must be passed systematically, namely the preparation phase, the implementation phase, observation, evaluation, and reflection. Data collection techniques through observation, interviews, questionnaires, and tests. The data analysis technique used is quantitative and qualitative techniques. The results of this study concluded that the HOTS of Science Education students in a fluid course increased with the module-assisted SETS approach with the results of the first cycle with an increase of 46% of the target, and the second cycle increased by 65% of the target. Fluid cognitive abilities can be improved through the application of the module-assisted SETS learning approach with a cognitive increase of 72%.